2016
DOI: 10.1038/tp.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and oculomotor performance in subjects with low and high schizotypy: implications for translational drug development studies

Abstract: The development of drugs to improve cognition in patients with schizophrenia is a major unmet clinical need. A number of promising compounds failed in recent clinical trials, a pattern linked to poor translation between preclinical and clinical stages of drug development. Seeking proof of efficacy in early Phase 1 studies in surrogate patient populations (for example, high schizotypy individuals where subtle cognitive impairment is present) has been suggested as a strategy to reduce attrition in the later stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 93 publications
4
20
0
Order By: Relevance
“…SPEM impairments in schizophrenia are well replicated (Levy, Sereno, Gooding, & O'Driscoll, ; O'Driscoll & Callahan, ). Similar deficits have been reported in overall high schizotypes (Koychev et al, ; Meyhöfer et al, ), in high positive, negative, and disorganized subgroups (Gooding, Miller, & Kwapil, ; Holahan & O'Driscoll, ; Lenzenweger & O'Driscoll, ; O'Driscoll, Lenzenweger, & Holzman, ; Smyrnis et al, ), and following sleep deprivation (Meyhöfer, Kumari, Hill, Petrovsky, & Ettinger, ).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…SPEM impairments in schizophrenia are well replicated (Levy, Sereno, Gooding, & O'Driscoll, ; O'Driscoll & Callahan, ). Similar deficits have been reported in overall high schizotypes (Koychev et al, ; Meyhöfer et al, ), in high positive, negative, and disorganized subgroups (Gooding, Miller, & Kwapil, ; Holahan & O'Driscoll, ; Lenzenweger & O'Driscoll, ; O'Driscoll, Lenzenweger, & Holzman, ; Smyrnis et al, ), and following sleep deprivation (Meyhöfer, Kumari, Hill, Petrovsky, & Ettinger, ).…”
Section: Introductionsupporting
confidence: 68%
“…Unexpectedly (Ettinger et al, ; Koychev et al, ), there were no schizotypy related differences in antisaccade performance. Possible reasons include less strict schizotypy inclusion criteria (Gooding, ; Holahan & O'Driscoll, ) and generally lower error rates in this study compared to prior research (Koychev et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Support for the importance and validity of studying correlates of schizotypy across the entire spectrum, including low scores, comes from the detection of the neural correlates of schizotypy in previous studies of low‐to‐medium scoring participants [Aichert et al, ]. Additionally, a recent study explicitly compared medium and low schizotypes to high schizotypes and demonstrated that low schizotypes can be differentiated from medium schizotypes, who in turn perform worse than high schizotypes, on smooth pursuit eye movements [Koychev et al, ], a key endophenotype and biomarker of schizophrenia [Calkins et al, ; Levy et al, ]. Thus, we feel that the observed relationships between rsFC and schizotypy scores in the low‐to‐moderate range may be indicative of associations that may emerge across the entire spectrum of schizotypy.…”
Section: Discussionmentioning
confidence: 99%